Silent as the grave - Bowen, Rhys; Broyles, Clare (Bowen, Rhys. Molly Murphy mysteries, 2025)
"Retired Detective Molly Murphy Sullivan goes undercover in the next book in the New York Times bestselling series from Rhys Bowen and Clare Broyles. With a newborn and two children, Molly Murphy Sullivan is tackling motherhood. Her husband, Daniel, is off to work in Washington as Easter break begins in New York. Her dear friend and writer, Ryan O'Hara, is shooting a movie, one of the first to involve a real plot and actors. He invites Molly and the children to visit the set and watch the excitement. When one of the actresses is fired, Molly's adopted daughter, Bridie, is called to replace her in the scene. Turns out she's a natural and is asked to star in the rest of the film. Molly is skeptical about leaving Bridie alone on set, but her great friends, Sid and Gus, offer to chaperone her. The movie industry is still experimenting with ways to get the best shot, like pretending to tie Bridie to real train tracks. But soon, their special effects start to malfunction. After a few mishaps where no one is hurt, the special effects turn deadly. With rumors of a feud between studios, Molly believes these malfunctions are sabotage. She is invited to go undercover on set to investigate the burgeoning film war. Once again, Rhys Bowen and Clare Broyles deliver an engaging mystery full of vibrant historical details and thrilling escapades featuring one of mystery's most beloved sleuths"--